Utilization of agricultural waste to reduce enteric methane emissions on livestock in tropical environment - Sulistyo .; Pranoto .; E. Mahajoeno; S.H. Pranolo; A. Sofyan; H. Herdian; B. Haryanto; R.H. Praptana (Global Journal of Environmental Science and Management, 2024)
BACKGROUND AND OBJECTIVES: The livestock sector contributes to increasing greenhouse gas emissions. The emissions generated from livestock mainly originate from enteric fermentation, which is strongly influenced by feed quality. The utilization of fermented rice straw as a source of crude fiber for animal feed is one solution for providing high-quality feed. Central Java is one of the centers of cattle farming and rice production in Indonesia. The purpose of this study was to determine the contribution of greenhouse gas emissions resulting from fermented straw feed formula commonly practiced by cattle farmers in Central Java.METHODS: Greenhouse gas production was conducted in vitro using three formulas arranged in a completely randomized design with six replications. The three feed formula treatments were: 30 percent king grass + 35 percent rice bran+ 35 percent wheat bran (treatment one), 30 percent fermented rice straw + 35 percent rice bran + 35 percent wheat bran (treatment two), and 30 percent fermented rice straw + 70 percent concentrate (treatment three). Feed nutrient content and enteric gas production were analyzed to determine the quality of the feed formula as well as to determine feed digestibility and greenhouse gas production during the digestion process. The gas production was measured at regular intervals of 8, 16, 24, 36, and 48 hours. The methane, nitrous oxide, and carbon dioxide contents were analyzed using gas chromatography. Data on nutrient content and digestibility of dry matter and organic matter were analyzed using analysis of variance, and the estimated greenhouse gas emissions were calculated using the ideal gas equation approach.FINDINGS: The quality of the feed formula influences the amountof greenhouse gases emission produced by enteric fermentation processes. The feed quality of treatment one was equivalent to that of treatment two. The treatment three feed formulation had a crude protein content approximately 3 percent higher than that of treatment one and treatment two. The digestibility of dry matter and organic matter values did not show significant differences between the treatments. The feed formula treatment two can reduce potential greenhouse gas emissions by 1.81 percent from treatment one, whereas treatment three can reduce potential greenhouse gas emissions by 27.78 percent from treatment one and by 26.4 percent from treatment two. These results indicate that feed formulas with higher crude protein content have greater potential to reduce greenhouse gas emissions. This finding can be used to mitigate and develop strategies to improve feed quality by utilizing agricultural waste as a broader low greenhouse gas emission livestock management effortCONCLUSION: Utilization of fermented straw has the potential to reduce greenhouse gas emissions resulting from enteric fermentation and contamination of unutilized straw waste and has the opportunity to reduce land use and greenhouse gas emissions from forage plants. Efforts to utilize fermented straw as a low greenhouse gas emission feed need to be followed by improvements in feed quality. More comprehensive studies need to be carried out on the variations in feed formulas based on differences in regional resources, the economic feasibility of utilizing fermented straw combined with various feed ingredients, and the life cycle assessment of straw utilization as a feed ingredient based on geographical, social, economic, technological, and environmental dimensions.